POLÍTICAS LINGUÍSTICAS ENTRE LÍNGUAS E MUNDOS: TERRITÓRIOS, SABERES E DISPUTAS - Faria, Vanessa Fabíola Silva de; Vieira, José Antônio; Oliveira Ribeiro, Mariana Aparecida de; Montiel Dominguez, Maria de Las Nieves (Revista de Letras Norte@mentos, 2026)
Apresentação